2008
DOI: 10.1007/s11090-008-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma Processing and Plasma Chemistry of Metallic Cobalt Surface

Abstract: Plasma processing of metallic cobalt was experimentally investigated with three fluorine-containing gases, CF 4 -O 2 , SF 6 -O 2 , and NF 3 to determine the surface decontamination rate and to examine the reaction mechanism. Results show that the maximum etching rate reaches 17.12 lm/min with NF 3 gas at 420°C, while the rates are 2.56 lm/min and 1.14 lm/min with CF 4 -O 2 and SF 6 -O 2 gas, respectively, at the same temperature. AES analysis identified the constituent elements of the reaction products to be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Since Fe 2p signals overlapped with F 1s, we characterized the Co 2p peaks instead, as shown in Figure b. It is found that the binding energy of Co 2p shifts from 778 eV to a higher level at ∼783 eV after activation, which should correspond to the formation of CoF 2 . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Fe 2p signals overlapped with F 1s, we characterized the Co 2p peaks instead, as shown in Figure b. It is found that the binding energy of Co 2p shifts from 778 eV to a higher level at ∼783 eV after activation, which should correspond to the formation of CoF 2 . , …”
Section: Resultsmentioning
confidence: 99%
“…It is found that the binding energy of Co 2p shifts from 778 eV to a higher level at ∼783 eV after activation, which should correspond to the formation of CoF 2 . 59,60 SEM and TEM were used to further characterize the morphology and structure of the cathode nanocomposite after its full activation at 4.5 V (Figure 7). After the fifth cycle, the FeCo/LiF/C composite still maintains the morphology of pristine composite spheres of pomegranate-like architecture (Figure 7a,b), demonstrating the robustness of this spherical nanostructure.…”
Section: Resultsmentioning
confidence: 99%
“…This result could be attributed to the formation of FeF 2 after overfluoridation, which is constant with the XRD result. Co 2p XPS spectra show the existence of Co 2+ in CoF 2 (Figure d), and the primary peaks centered at 783.1 and 799.1 eV are attributed to the spin–orbits of Co 2p 3/2 and Co 2p 1/2 , accompanied by satellite peaks . Moreover, two weak peaks at 782.0 and 798.1 eV may be ascribed to partial surface oxidation .…”
Section: Resultsmentioning
confidence: 95%
“…A CoFe precursor shows the typical diffraction peaks of Co−Fe hydroxyl carbonates (Figure S6 and the primary peaks centered at 783.1 and 799.1 eV are attributed to the spin−orbits of Co 2p 3/2 and Co 2p 1/2 , accompanied by satellite peaks. 34 Moreover, two weak peaks at 782.0 and 798.1 eV may be ascribed to partial surface oxidation. 35 The peak at 684.62 eV arises from the formed the metal−F bond in the F 1s spectra (Figure S8a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the maximum degree of fluorination of Cr 2 O 3 is very small even after hundreds of hours of contact time. In contrast, Y 2 O 3 , Co 3 O 4 , La 2 O 3 and ZnO could be easily fluorinated to YF 3 [28], CoF 2 [29], LaF 3 [30] and ZnF 2 [31]. However, note that the content of the promoter M is Considering that crystalline phase Cr 2 O 3 could not be reduced below 800 8C in H 2 atmosphere [32], the reduction peak of Cr 2 O 3 catalyst is probably attributed to the easily reducible Cr(VI) species.…”
Section: Introductionmentioning
confidence: 99%